Effect of Adhesive Boosters on Bond Strength of Bleached Teeth in Orthodontic Bonding. Issue 1 (January 2022) - Ranganayakulu, I; Varma, D Praveen Kumar; Priya CV, Padma; Ram, RSVM Raghu; Viswanadh, K Anand; Harsha, GV Durga
Objectives: To evaluate and compare the effect of adhesion boosters on shear bond strength (SBS) of orthodontic brackets on bleached teeth. Materials and Methods: A sample of 90 extracted maxillary premolars was equally divided into 2 groups of bleached and non-bleached teeth. Twenty-two percent carbamide peroxide gel was used as an agent for bleaching. Each group was further divided equally into 3 subgroups depending on the type of adhesive booster used (Enhance LC, All-bond 2, and no adhesive booster [control]) and maxillary premolars brackets were bonded. Debonding was done with a universal testing machine, and the SBS was recorded. Results: The SBS of non-bleached teeth was highest for All-bond 2 (14.78± 2.47 MPa) followed by Enhance LC (13.15 ± 3.49 MPa) and control (10.30 ± 1.06 MPa). The SBS of bleached teeth was highest for All bond 2 (12.23 ± 1.41 MPa) followed by Enhance LC (11.76 ± 1.71 MPa) and control (9.63 ± 1.06 MPa). All subgroups showed a significant difference in SBS (P = .000) on bleached and non-bleached teeth. The SBS showed a significant difference between the bleached and non-bleached teeth in All-bond 2 group (P = .019). Conclusion: Adhesive boosters increased the SBS of both bleached and non-bleached teeth significantly. Among the two adhesive boosters used, All-bond 2 showed more SBS values.